"Betwixt and Between:" The Challenges of Public Ethnographic Writing about Argentina. (23rd April 2015) - Zaretsky, Natasha
Abstract : This essay offers a series of reflections about the challenges that arise for an ethnographer writing in the public sphere, especially when addressing controversial issues or moments of political uncertainty in sites of long-term fieldwork. In this case, Argentina, where the author has conducted fieldwork for over fourteen years, experienced a political crisis stemming from the unexplained death of a prosecutor in January 2015. In such moments of crisis, this essay asks, what is the role and responsibility of the academic voice? Inevitably, challenges arise when presenting ethnographically inflected work for a public audience, often leaving the author in a liminal space, "betwixt and between" the academic world and the public sphere. Yet, these challenges and liminal spaces can also expand the boundaries of one's field of study, engaging new audiences while also offering powerful insights into the production of academic knowledge.